Aloe vera is non-toxic to cells: A microculture tetrazolium technique colorimetric assay study - Devi Gopakumar; Sunil Sukumaran Nair (Wolters Kluwer Medknow Publications, 2014)
Introduction: Aloe vera (Av), a succulent of Liliaceae family is now a widely used medicinal plant. Its' application covers a wide spectrum of human diseases, including oral mucosa, gastric mucosa and skin. Aloe vera preparations in the form of gel, mouth washes and cream are applied topically for many oral diseases. The applications include oral lichen planus, candidiasis, oral submucous fibrosis, geographic tongue, etc. Aims and Objectives: To evaluate the cytotoxicity of Av on human fibroblasts. Materials and Methods: Aloe vera preparation (70%) was applied on the fibroblast cell lineage and the cell viability was evaluated by microculture tetrazolium technique (MTT) colorimetric assay. Results: The cell viability at different concentrations was measured. The cells have maintained their viability at different concentrations used in the study. Conclusion: Our study shows the cell viability at different sample concentrations of Av. This could open up wide clinical applications of Av for reactive, inflammatory and potentially malignant oral and other mucocutaneous diseases.